Dialogue-building technique to increase oral fluency through pair work - Tinoco Añazco, Julia Rosa (2012)
This study have as main purpose take into account the current methodology, the design of a technique in order to develop oral skills in learning the English language among students, according to a new educational model designed. With the proposed technique, the author provides teachers and students with a number of different kinds of activities focused on speaking skills, such as : conversations, pair work, group work, class activities, and role plays which can contribute to the development of oral communication.